Terrible magnificent sociology - Wade, Lisa (Professor) (W.W. Norton & Company, 2022)
"Using engaging stories and a diverse cast of characters, Lisa Wade memorably delivers what C. Wright Mills described as both the terrible and magnificent lessons of sociology. With chapters that build upon one another to form a compelling and seamless narrative, Terrible Magnificent Sociology represents a new kind of introduction to sociology. Recognizing the many statuses students carry, Wade goes beyond race, class, and gender, considering inequalities of all kinds-and their intersections. She also highlights the remarkable diversity of sociology, not only of its methods and approaches but also of the scholars themselves, emphasizing the contributions of women, immigrants, and people of color"--